2013
DOI: 10.1186/1479-5868-10-135
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the psychological and social benefits of participation in sport for adults: informing development of a conceptual model of health through sport

Abstract: BackgroundThe definition of health incorporates the physical, social and mental domains, however the Physical Activity (PA) guidelines do not address social health. Furthermore, there is insufficient evidence about the levels or types of PA associated specifically with psychological health. This paper first presents the results of a systematic review of the psychological and social health benefits of participation in sport by adults. Secondly, the information arising from the systematic review has been used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
347
4
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 422 publications
(372 citation statements)
references
References 21 publications
11
347
4
10
Order By: Relevance
“…Other studies have suggested that sports participation could give adolescents an enhanced sense of mastery, which in turn could increase their self-esteem (8,12,30,31). A heightened feeling of belonging to an extended group, which goes beyond simply increasing the number of friends one has, has also been suggested as a contributing factor (8,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have suggested that sports participation could give adolescents an enhanced sense of mastery, which in turn could increase their self-esteem (8,12,30,31). A heightened feeling of belonging to an extended group, which goes beyond simply increasing the number of friends one has, has also been suggested as a contributing factor (8,12).…”
Section: Discussionmentioning
confidence: 99%
“…Research showing a positive effect of physical activity on mental health among adolescents is well documented (4)(5)(6)(7)(8). A study conducted in Iceland revealed that adolescents who often practiced sports had a more positive body image and were more likely to report a healthy mental condition (9).…”
Section: Introductionmentioning
confidence: 99%
“…As Shank (2009, p.7) notes, "sport has become one of the most important and universal institutions in our society", linking together industries, governments and consumers in mutually-beneficial, increasingly visible and highly valuable ways. These range from sport's mediating role as an avenue for social justice and facilitator of health through participation, right through to its attractive qualities for brand alignment and mass communication (Eime et al, 2013;Widdop et al, 2016 (Hutchins and Rowe, 2012;Milne, 2016). These platforms, from established analogue players to new digital operators, see their audiences as networks of brands and consumers that can be parlayed together when an attractive product such as sport is on offer.…”
Section: Background and Current Sport Environmentmentioning
confidence: 99%
“…Participation is associated with positive health outcomes and the development of aspirational qualities such as team work, leadership, perseverance and the pursuit of excellence (Eime et al, 2013;Holt et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…La literatura científica ofrece un conjunto de evidencias que sustentan el carácter potencialmente saludable de la práctica regular de ejercicio físico (Eime, Young, Harvey, Charity, y Payne, 2013;Hötting y Röder, 2013). No obstante, la investigación también ha mostrado que el ejercicio físico puede contribuir a la aparición de consecuencias menos deseables cuando éste se realiza de una forma obsesiva y repetitiva (Paradis, Cooke, Martin, y Hall, 2013).…”
unclassified